Blended learning and assessment in medical education: important for Nepal - Pathyil, Ravi Shankar (Janaki Medical College Journal of Medical Science, 2021)
The outbreak of the coronavirus disease-19 (COVID-19) pandemic in early 2020 caused an abrupt shift to online teaching-learning globally. Nepal was no exception. Like most other countries Nepal has gone through multiple waves of the pandemic and the latest surge led by the Omicron variant started in January 2022. Due to the lockdown in March 2020 and the absence of physical in-person classes, medical colleges in Nepal had to shift overnight to online teaching-learning.